Difference Sequence Spaces Generated by ϕ−Function and Their Bi-complex Extension (The Nepali Mathematical Sciences Report, 2025)
Classical sequence spaces such as l∞ , c, and c0 have been extensively studied and recognized as fundamental in the advancement of functional analysis and related areas of mathematics. In this article, we investigate the algebraic properties together with para- norm structures of the sequence spaces W0 (∆, f )(C2), W (∆, f )(C2), and W∞ (∆, f )(C2) in a bi-complex setting, which are induced by a non-negative real-valued function ϕ.